The Significance of Village Data for Village Development: Students’ Community Development Program Experience (Kuliah Kerja Lapangan) – Universities Contribution to Village Development - Tutik Rachmawati; Trisno Sakti Herwanto; Kristian Widya Wicaksono (Magister Administrasi Publik, 2017)
It is common knowledge that development planning at the village level is rarely based on valid and updated data. Students and lecturers in the Public Administration Department Parahyangan Catholic University, who have been working with villages in West Java Province for several decades encountered situations to support that argument. It is difficult to obtain valid and updated data to use as evidence in developing initiatives and programs for the village development. Students’ Community Development Program (Kuliah Kerja Lapangan henceforth KKL themed Universities Contribution to Village Development was initiated with the goal of improving the quality of data in rural areas (Garut District) by collecting and updating village data, developing the capacity of village government leaders and staff to collect and update village data on their own. This paper discusses three major works that the Students’ Community Development Program (KKN) themed Universities Contribution to Village Development have made. The three areas relate to 1) elaboration of the logic of the program; (2) discussion of the process of data collection and analysis of data in the three villages; and (3) discussion of output and outcomes of the program. Research action, as Lewin argues, has three goals: to advance knowledge; to improve a concrete situation; and to improve behavioral science methodology. This paper presents a case study that shows the existence of a problem in a community, and concrete actions taken to solve it through the application of knowledge acquired through Community Development Program (KKL) experience of Universitas Membangun Desa.